Pengendalian Hama dan Gulma Menggunakan Pertanian Terpadu Padi-Itik-Azolla - Etty Safriyani; Mery Hasmeda; Munandar Munandar; Firdaus Sulaiman; Holidi Holidi (Seminar Nasional Lahan Suboptimal, 2019)
Safriyani E, Hasmeda M, Munandar M, Sulaiman F, Holidi H. 2019. Pests and weeds controlling using integrated rice-duck-azolla farming. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 71-78. Palembang: Unsri Press.Pests and weeds can reduce plant growth and production. Integrated Rice-duck-azolla farming is biologically controller of pests and weeds in rice plants. The research aims to evaluate the role of ducks and azollas in reducing pest and weed populations of rice plants. The research has been carried out in the irrigated rice fields of Tanah Periuk Village, Muara Beliti District, Musi Rawas Regency from October 2018 to February 2019. The study used experimental method with a randomized block design, consisting of K1= 250 kg urea/ha: without ducks and azolla, K2 = 187.5 kg urea/ha: without ducks: azolla 1000 kg/ha, K3 = 187.5 kg urea/ha: duck 3000/ha: azolla 1000 kg/ha, K4 = 125 kg urea/ha: duck 3000/ha: azolla 1000 kg/ha, K5 = 62.5 kg urea/ha: duck 3000/ha: azolla 1000 kg/ha, K6 = without N: duck 3000/ha: azolla 1000 kg/ha. The application of 3000 ducks/ha and 1000 kg/ha azolla could reduce rice pests and weeds, including Nephotettix virescens 83.33%, Valanga SP 88.70% dan Scirpophaga innotata 83.57%, Fimbristylis dichotoma 84%,  Cyperus difformis 91.4%, Ludwigia adscendens 85.7% and Eclipta prostrata 80.8%.Keywords: azolla, duck, integrated farming, pest